2016
DOI: 10.5433/1679-0375.2016v37n1p45
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento Avançado de Efluente de Reator UASB por Membrana de Microfiltração Associado à Desinfecção por Radiação Ultravioleta

Abstract: ResumoA baixa eficiência dos reatores UASB, no que se refere às remoções de nutrientes, patogênicos e matéria orgânica, faz com que seja necessário o pós-tratamento, a fim de melhorar a qualidade do efluente gerado. Assim sendo, investigou-se nesse estudo a utilização da microfiltração associada à desinfecção por radiação ultravioleta como alternativa ao tratamento avançado de esgotos. Para isso, foram coletadas amostras de efluente de reator UASB a fim de realizar ensaios em sistema piloto de microfiltração, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The Vila 3 Marias WWTP (UASB + Chlorination) obtained a satisfactory result in the reduction of pathogens according to the legislation, only in the months of April (100 CFU/100 mL) and June (1 CFU/100 mL), the E. coli values in the treated effluent being still quite high when compared with some authors [32,33]. Anaerobic reactors are not designed for the purpose of removal of microorganisms, this being a consequence of the retention of solids [14].…”
Section: E Colimentioning
confidence: 96%
“…The Vila 3 Marias WWTP (UASB + Chlorination) obtained a satisfactory result in the reduction of pathogens according to the legislation, only in the months of April (100 CFU/100 mL) and June (1 CFU/100 mL), the E. coli values in the treated effluent being still quite high when compared with some authors [32,33]. Anaerobic reactors are not designed for the purpose of removal of microorganisms, this being a consequence of the retention of solids [14].…”
Section: E Colimentioning
confidence: 96%
“…The literature indicates that UV radiation has been used as an important tool for microbiological control in several areas, as in sanitary sewage, rainwater, and effluent treatments. 23,24,44 In many cases it was found that UV radiation can achieve effectiveness of more than 90% against E. coli, C. perfringens and total coliforms. 24 In this study it was found that UV radiation can achieve 99% efficiency in diesel oil treatment against microorganisms.…”
Section: Commercial Application and Technology Challengesmentioning
confidence: 99%
“…Many studies have reported the use of UV irradiation for the disinfection of aqueous media. The technique has been applied to domestic effluents, to inactivate the eggs of Ascaris sp., 22 as well as for sewage disinfection, 23 and for the post‐treatment of an upflow anaerobic sludge blanket (UASB) reactor, and the effects on Escherichia coli , Clostridium perfringens , total coliforms, and coliphages in effluent have been evaluated 24 . However, an extensive literature search found no studies of the use of UV radiation to control microorganisms in fuels.…”
Section: Introductionmentioning
confidence: 99%